2007
DOI: 10.1161/circulationaha.106.665836
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Polymorphism in the 3′UTR of the l -Arginine Transporter Gene SLC7A1

Abstract: Background-Endothelial dysfunction because of reduced nitric oxide bioavailability is a key feature of essential hypertension. We have found that normotensive siblings of subjects with essential hypertension have impaired endothelial function accompanied by altered arginine metabolism. Methods and Results-We have identified a novel C/T polymorphism in the 3ЈUTR of the principal arginine transporter, solute carrier family 7 (cationic amino acid transporter, yϩ system), member 1 gene (SLC7A1). The minor T allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 26 publications
3
61
1
4
Order By: Relevance
“…We recently demonstrated that superoxide dismutase inhibition augmented oxidative stress and increased arterial pressure in mice. 50 Of note, we found that transgenic mice with augmented endothelial-specific l-arginine transport 51 were resistant to the development of superoxide dismutase inhibition-induced oxidative stress. 50 These findings indicate that augmenting endothelial-specific l-arginine transport can prevent oxidative stress in addition to augmenting NO bioavailability.…”
Section: Reduced No Bioavailability Can Lead To Oxidative Stressmentioning
confidence: 79%
See 1 more Smart Citation
“…We recently demonstrated that superoxide dismutase inhibition augmented oxidative stress and increased arterial pressure in mice. 50 Of note, we found that transgenic mice with augmented endothelial-specific l-arginine transport 51 were resistant to the development of superoxide dismutase inhibition-induced oxidative stress. 50 These findings indicate that augmenting endothelial-specific l-arginine transport can prevent oxidative stress in addition to augmenting NO bioavailability.…”
Section: Reduced No Bioavailability Can Lead To Oxidative Stressmentioning
confidence: 79%
“…Furthermore, a functionally relevant genetic polymorphism relating to l-arginine transport is present in human essential hypertension. 51 We have previously shown that l-arginine transport, assessed both in vivo and in vitro, is reduced not only in hypertensive subjects but also in those that are genetically predisposed to hypertension. 64 Although this study did not specifically address obesity-related hypertension, hypertensive subjects had a greater body mass index than their normotensive counterparts.…”
Section: Are No Bioavailability and L-argininementioning
confidence: 99%
“…For example, some patients with congestive heart failure have an abnormality in L-arginine transport due to a decreased level of Cat-1 mRNA (4). Furthermore, a recently identified cytosine to uracil polymorphism in the 3Ј-untranslated region (3Ј-UTR) 2 of the human Cat-1 mRNA seems to attenuate its expression level and contributes to hypertension and endothelial dysfunction (5). Elevated Cat-1 expression has also been reported to contribute to the pathogenesis of kidney hyperfiltration in diabetic rats.…”
mentioning
confidence: 99%
“…Examples include our data for the T825 allele of the C285T polymorphism of the G-protein ␤3 subunit gene (GNB3) with hypertension and blood pressure, 90 the A1166C variant of the angiotensin II type 1 receptor gene (AGTR1), 91 and the T-344C and A6547G polymorphisms of the aldosterone synthase gene (CYP11B2), especially after analysis of haplotypes, 92 among others. [93][94][95][96][97][98] It also might have helped explain why we found no association with hypertension in the case of polymorphisms in certain additional genes for which positive association findings had been reported. 99 -105 Our glucocorticoid receptor gene (NR3C1) data were, however, weak.…”
Section: Importance Of Choosing Only Subjects With Two Hypertensive Pmentioning
confidence: 74%